Composite matrices for promoting neurodistribution, osteogenesis and angiogenesis

By combining elastin-like peptides, bioactive peptides and calcium phosphate in the hydrogel, a complex matrix that can recruit neurons and endothelial cells is solved, and the problems of insufficient cell colonization uniformity and material degradation are achieved. Osteogenic performance, nerve distribution and promotion of vascularization in engineering.

CN119212743APending Publication Date: 2024-12-27INST POLYTECHN DE BORDEAUX +3
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202380035558.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-04-22
Filing Date
2023-04-21
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

Existing hydrogels have problems with insufficient cell colonization uniformity and poor biodegradability of materials in promoting nerve distribution, tissue vascularization and osteogenesis.

Method used

Develop a composite matrix containing elastin-like peptides, bioactive peptides and calcium phosphate, and prepare elastin-like peptides and adhesion peptides with alkenyl methionine residues through genetic engineering, combining with calcium phosphate mineral phase to form recruitment Biocompatible complex matrix of sensory neurons and endothelial cells.

Benefits of technology

A more uniform cell colonization is achieved, the biodegradability of the material is improved, and the osteogenic performance in bone engineering is demonstrated, promoting nerve distribution and tissue vascularization.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The present invention provides a composite material useful for promoting nerve distribution, osteogenesis and angiogenesis.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a composite matrix that can be used to promote innervation, osteogenesis and angiogenesis. Background Art

[0002] Using a co-culture model of sensory neurons, mesenchymal cells, and endothelial cells, our team (Silva et al., Cell Death and Disease, 2017 Dec 13;8(12):3209; Leroux et al., Cell Commun Signal. 2020 Oct 19;18(1):162) demonstrated the influence of communication between these three cell types on osteogenesis and the importance of neurovascular dialogue for osteogenesis. Based on these observations, the team developed an elastin peptide-based hydrogel that stimulates the recruitment of nerve fibers, especially sensory neurons (Paiva dos Santos et al., Acta Biomaterialia, 2019 Nov;99:154-167; PCT / EP2019 / 055075), and can be adapted to other cell types. With this in mind, the inventors attempted to improve various properties of the hydrogel, particularly in terms of uniformity of cell colonization and improving the biodegradability of the material, and proposed a biocompatible, injectable composite matrix that can stimulate innervation, tissue vascularization, and exhibit osteogenic properties for application in bone engineering. Summary of the invention

[0003] The inventors have developed a novel composite material comprising an organic phase and a mineral phase. This material is biocompatible, injectable, can stimulate innervation and tissue vascularization, and exhibits osteogenic properties for bone engineering. More specifically, the present invention relates to a composite matrix that combines an organic phase functionalized with a bioactive peptide and a mineral phase comprising calcium phosphate. The composite matrix according to the present invention is capable of recruiting sensory neurons and acting as a host for osteoblasts and endothelial cells. DETAILED DESCRIPTION

[0004] The composite matrix according to the invention is characterized in that it contains an organic phase comprising an elastin-like peptide, at least one bioactive peptide, and a mineral phase comprising calcium phosphate.

[0005] 1. Elastin-like peptide

[0006] The first component of the composite matrix according to the invention is an elastin-like peptide (or ELP, i.e., elastin-like polypeptide) which, before the composite matrix is ​​formed, contains at least one olefinated methionine residue. Peptides of this type, their preparation by genetic engineering and their purification are known to those skilled in the art, in particular reference may be made to the international application WO2017021334 and the articles of Petitdemange et al. (Biomacromolecules. 2017 Feb 13; 18(2): 544-550) and Petitdemange et al. (Bioconjug Chem. 2017 May 17; 28(5): 1403-1412). The skilled person may also refer to the examples presented below relating to the production of an ELP referred to as ELPM80.

[0007] In the context of the present invention, the term "alkenylated methionine residue" means that the side chain of the methionine residue is covalently bonded to a moiety comprising an alkenyl group, i.e. a group comprising at least one double bond between two carbon atoms. Preferably, the term "alkenyl" refers to the presence of a -CH=CH2 group in the moiety to which the methionine residue is attached. According to a particular embodiment, the methionine moiety is attached to a moiety of formula (I):

[0008] (I)

[0009] According to one embodiment, the partially synthesized olefinated ELP of formula (I) can be prepared by chemically selectively thioalkylating the methionine side chain using allyl glycidyl ether according to the procedure described in Petitdemange et al. (Bioconjug Chem. 2017 May 17; 28(5): 1403-1412). Specifically, the skilled person can refer to the examples of the present application to perform thioalkylating the ELP peptide referred to as ELPM80.

[0010] According to one embodiment, the alkenylated ELP implemented in the present invention comprises at least one occurrence of the amino acid sequence VPGMG, wherein the methionine residue is alkenylated.

[0011] According to a particular embodiment, the alkenylated ELP used to prepare the composite matrix according to the invention is an ELP with a high molecular weight, in particular a molecular weight higher than 20 kDa.

[0012] In one embodiment, the olefinated ELP has a structure of formula (II):

[0013] Z-[VPGXG] n (II)

[0014] in:

[0015] Z is a peptide comprising 1 to 20 amino acids;

[0016] X represents a glycine residue, a valine residue or an alkenylated methionine residue, in particular an alkenylated methionine residue of formula (III):

[0017] (III);

[0018] n is an integer between 40 and 160, more particularly between 60 and 100, in particular between 70 and 90; and

[0019] The molar ratio of valine / alkenylated methionine at position X is between 0:1 and 10:1, more particularly between 1:1 and 5:1, in particular between 2:1 and 4:1, more particularly the ratio is 3:1.

[0020] According to one embodiment, X represents a glycine residue or an alkenylated methionine residue, in particular an alkenylated methionine residue of formula (III). According to another preferred embodiment, X represents a valine residue or an alkenylated methionine residue, in particular an alkenylated methionine residue of formula (III).

[0021] According to one embodiment, n is an integer between 60 and 100, in particular between 70 and 90, more in particular between 76 and 84, more in particular n is equal to 76, 77, 78, 79, 80, 81, 82, 83 or 84. More in particular, n is equal to 80.

[0022] According to a specific embodiment, Z is a peptide whose amino acid residue at the amino terminus is methionine. According to another embodiment, the Z comprises a peptide immediately adjacent to [VPGXG] n The amino acid upstream of the unit corresponds to a MW dipeptide. In particular, Z may consist of or comprise a MW dipeptide. In a specific embodiment, Z consists of a MW dipeptide.

[0023] According to one embodiment, the ELP used is of the formula Z-[VPGXG] n A peptide wherein the molar ratio of valine / alkenylated methionine at position X is between 1:1 and 5:1, in particular between 2:1 and 4:1, more particularly the ratio is 3:1.

[0024] According to another embodiment, the ELP used is of the formula Z-[(VPGVG)(VPGMG)(VPGVG) 2 ] x , especially MW[(VPGVG)(VPGMG)(VPGVG) 2 ]x A peptide wherein x is an integer between 15 and 25, in particular between 19 and 21, more particularly x is equal to 20.

[0025] According to one embodiment, the ELP used is derived from the peptide MW [(VPGVG)(VPGMG)(VPGVG) described in the Examples 2 ] 20 (ELPM80), the peptide comprising at least one olefinated methionine residue. According to another specific embodiment, the ELP used has the formula MW [(VPGVG)(VPGMaG)(VPGVG) described in the examples 2 ] 20 (ELPM(olefin)-80), wherein Ma represents an olefinated methionine residue of the above formula (III).

[0026] According to a particular embodiment, the composite matrix according to the invention comprises 0.1 to 99.9% (w / v) of ELP. According to another particular embodiment, for a concentration between 3 and 5% (w / v) and a thiol:olefin ratio of 1:1, the matrix comprises 1 to 4% (w / v) of ELP, in particular ELPM80,

[0027] 2. Bioactive Peptides

[0028] The composite matrix may also contain bioactive peptides. When the composite matrix is ​​implanted into a tissue or organ of a subject, the bioactive peptides are capable of performing biological functions. Such bioactive peptides may specifically be adhesion peptides or calcium binding peptides capable of binding to cells of interest.

[0029] These bioactive peptides included in the composite matrix of the present invention can contain cysteine ​​residues at each of their ends. The cysteine ​​residues can be covalently linked to the amino acid sequence of the peptide directly or through a spacer (particularly a peptide or pseudopeptide spacer). Particularly, the spacer can be an amino acid or an amino acid sequence (particularly a dipeptide or a tripeptide), particularly a β amino acid, more particularly a β-Ala amino acid.

[0030] According to a particular embodiment, the amount of biologically active peptide in the composite matrix according to the invention is between 99.9 and 0.1% (w / v). According to another particular embodiment, for a concentration between 3 and 5% (w / v) and a thiol: olefin ratio of 1:1, the matrix comprises between 0.1 and 3% (w / v) of said at least one biologically active peptide.

[0031] 2.1. Adhesion peptides

[0032] The first class of bioactive peptides that can be used in the composite matrix of the present invention is an adhesion peptide that can recruit neurons, mesenchyme and / or endothelial cells. As peptides that can recruit endothelial cells, it is particularly possible to mention peptides derived from laminin, fibronectin or type I collagen, more particularly laminin. Therefore, the adhesion peptide can be selected from the fibronectin derived peptides REDV, RGD and GRGDSP, the laminin derived peptides IKLLI, IKVAV, PDSGR and YIGSR, and the type I collagen derived peptide DGEA. As peptides that can recruit neuronal cells, it is particularly possible to mention the laminin derived peptides YIGSR, RNIAEIIKDI and IKVAV.

[0033] In a preferred embodiment, the composite matrix comprises at least one adhesion peptide selected from the group consisting of IKVAV and YIGSR.

[0034] According to a specific embodiment, the adhesion peptide is an IKVAV peptide. Specifically, the IKVAV peptide can be an IKVAV peptide of the formula Cys-{spacer}-Ile-Lys-Val-Ala-Val-{spacer}-Cys, in particular a peptide of the formula Cys-{β-Ala}-Ile-Lys-Val-Ala-Val-{β-Ala}-Cys.

[0035] According to another specific embodiment, the adhesion peptide is a YIGSR peptide. Specifically, the YIGSR peptide can be a YIGSR peptide of the formula Cys-{spacer}-Tyr-Ile-Gly-Ser-Arg-{spacer}-Cys, in particular a peptide of the formula Cys-{β-Ala}-Tyr-Ile-Gly-Ser-Arg-{β-Ala}-Cys.

[0036] According to an even more preferred embodiment, said composite matrix comprises said IKVAV peptide and said YIGSR peptide.

[0037] According to a preferred alternative embodiment, in order to optimize and control the cross-linking of the composite matrix, the latter comprises a single adhesive peptide containing at least two adhesive peptides, in particular a biomimetic peptide comprising the adhesive peptides IKVAV and YIGSR. The peptides constituting the single adhesive peptide may be included in any order. According to an alternative embodiment, the single adhesive peptide comprises the peptides YIGSR and IKVAV from the amino terminus to the carboxyl terminus. In a preferred alternative embodiment, the single adhesive peptide comprises the peptides IKVAV and YIGSR from the amino terminus to the carboxyl terminus. The single adhesive peptide may comprise a cysteine ​​residue at each of its ends. The cysteine ​​residue may be covalently linked to the amino acid sequence of the single adhesive peptide directly or through a spacer (in particular a peptide or pseudopeptide spacer). In particular, the spacer may be an amino acid or an amino acid sequence (in particular a dipeptide or tripeptide), in particular a β amino acid, more particularly a β-Ala amino acid. In addition, the peptides constituting the single adhesive peptide may be covalently linked to each other directly or through a spacer. The spacer between the peptides constituting the single adhesion peptide may in particular be a peptide or pseudopeptide spacer, in particular a glycine amino acid, diglycine or triglycine.

[0038] Furthermore, in advantageous cases, the single adhesion peptide comprising at least two adhesion peptides may comprise one or more target sequences of one or more metalloproteinases, in particular metalloproteinases 2 and 9. By way of example, the following peptides may be mentioned:

[0039] - PVGLIG;

[0040] - the peptides QPQGLAK, GPLGLSLGK and GPLGMHGK described in Jha et al., Biomaterials, May 2016; 89; p. 136-47; and

[0041] - Peptides GPQGIAGQ, GPQGIWGQ and VPMSMRGG described in Lin et al., Acta Biomaterialia, 10(12), December 2014, p. 5106-5115.

[0042] Such metalloproteinase target peptides can be introduced to achieve cleavage between adhesion peptides, which can be used for cell adhesion while still binding to the matrix of the present invention. In addition, metalloproteinase target peptides may be used to trigger matrix degradation, thereby promoting cell colonization. The metalloproteinase target peptide can be included in any position of the single adhesion peptide, particularly at its amino terminus, between two adhesion peptides included in the single adhesion peptide, or at its carboxyl terminus. Preferably, the metalloproteinase target peptide is located between two adhesion peptides in the single adhesion peptide.

[0043] According to a particular embodiment, the single adhesion peptide comprises at least one occurrence, in particular a single occurrence, of the target sequence PVGLIG for metalloproteinases 2 and 9.

[0044] According to a specific embodiment, the composite matrix comprises a single adhesion peptide comprising peptides IKVAV, PVGLIG and YIGSR. According to a specific embodiment, the single adhesion peptide has the following formula:

[0045] IKVAV(spacer)PVGLIG(spacer)YIGSR;

[0046] YIGSR(spacer)PVGLIG(spacer)IKVAV;

[0047] PVGLIG(spacer)YIGSR(spacer)IKVAV;

[0048] PVGLIG(spacer)IKVAV(spacer)YIGSR;

[0049] IKVAV(spacer)YIGSR(spacer)PVGLIG; or

[0050] YIGSR(spacer)IKVAV(spacer)PVGLIG.

[0051] Preferably, the single adhesion peptide has the formula IKVAV(spacer)PVGLIG(spacer)YIGSR.

[0052] The spacers referred to as "(spacers)" in the unique sequences listed above may have the same or different sequences, in particular the same sequence. In particular, the spacers may be selected from a glycine residue, a diglycine dipeptide or a triglycine tripeptide.

[0053] According to an alternative embodiment, the single adhesion peptide has the following formula:

[0054] IKVAV-GGG-PVGLIG-GGG-YIGSR;

[0055] YIGSR-GGG-PVGLIG-GGG-IKVAV;

[0056] PVGLIG-GGG-YIGSR-GGG-IKVAV;

[0057] PVGLIG-GGG-IKVAV-GGG-YIGSR;

[0058] IKVAV-GGG-YIGSR-GGG-PVGLIG; or

[0059] YIGSR-GGG-IKVAV-GGG-PVGLI.

[0060] Preferably, the single adhesion peptide has the formula IKVAV-GGG-PVGLIG-GGG-YIGSR.

[0061] Prior to cross-linking and formation of the composite matrix, the peptide capable of introducing the single peptide into the composite matrix may have the following formula:

[0062] CβA-IKVAV(spacer)PVGLIG(spacer)YIGSR-βAC;

[0063] CβA-YIGSR(spacer)PVGLIG(spacer)IKVAV-βAC;

[0064] CβA-PVGLIG(spacer)YIGSR(spacer)IKVAV-βAC;

[0065] CβA-PVGLIG(spacer)IKVAV(spacer)YIGSR-βAC;

[0066] CβA-IKVAV(spacer)YIGSR(spacer)PVGLIG-βAC; or

[0067] CβA-YIGSR(spacer)IKVAV(spacer)PVGLIG-βAC.

[0068] Preferably, the peptide capable of introducing the single peptide into the hydrogel may have the formula CβA-IKVAV(spacer)PVGLIG(spacer)YIGSR-βAC prior to cross-linking and formation of the composite matrix.

[0069] In a preferred embodiment, the peptide capable of introducing the single peptide into the composite matrix prior to cross-linking and formation of the composite matrix has the following formula:

[0070] CβA-IKVAV-GGG-PVGLIG-GGG-YIGSR-βAC;

[0071] CβA-YIGSR-GGG-PVGLIG-GGG- IKVAV-βAC;

[0072] CβA-PVGLIG-GGG-YIGSR-GGG-IKVAV-βAC;

[0073] CβA-PVGLIG-GGG-IKVAV-GGG-YIGSR-βAC;

[0074] CβA-IKVAV-GGG-YIGSR-GGG-PVGLIG-βAC; or

[0075] CβA-YIGSR-GGG-IKVAV-GGG-PVGLIG-βAC.

[0076] Particularly preferably, the peptide capable of introducing the single peptide into the composite matrix prior to crosslinking and formation of the composite matrix has the formula CβA-IKVAV-GGG-PVGLIG-GGG-YIGSR-βAC.

[0077] In a particular embodiment, the amount of peptide used to introduce the single peptide into the composite matrix according to the invention is between 99.9 and 0.1% (w / v). Depending on the composition of the single peptide and the presence of other biologically active peptides, and for a given composite matrix concentration, a person skilled in the art will of course be able to adjust the amount of the single peptide.

[0078] 2.2. Peptides capable of inducing calcium phosphate nucleation

[0079] Peptides capable of inducing calcium phosphate nucleation constitute a second class of bioactive peptides that can be introduced into the composite matrix according to the invention. The experiments provided below show that in the composite matrix according to the invention, the distribution uniformity and retention of calcium phosphate are improved in the presence of such peptides capable of inducing calcium phosphate nucleation. In particular, it was shown that surprisingly, in the presence of the SNA15 peptide, about 10 times more hydroxyapatite particles were found in the matrix, which can have a beneficial effect on the osteoconductive and / or osteoinductive properties of the composite matrix.

[0080] For the purpose of composite matrix formation, they may be included in a single peptide also comprising at least one adhesion peptide, or constitute separate peptides. In a preferred embodiment, the peptide capable of inducing calcium phosphate nucleation is a peptide that is not bound to an adhesion peptide prior to composite matrix formation.

[0081] By way of example, among the peptides capable of inducing calcium phosphate nucleation, mention may be made of:

[0082] - peptides derived from statherin as described in Raj et al., JBC, volume 267(9), March 25 1992, Pages 5968-5976, in particular DDDEEKFLRRIGRFG (SNA15) and SNA15 analogs, more particularly the peptides DSSEEKFLRRIGRFG (SNS15) and EFLRRIGRFG (SN11);

[0083] - Peptide DHTKE (Sun et al., Journal of Agricultural and Food Chemistry 2017 65(44), 9782-9789);

[0084] - Peptide SSSEEIVPN (Meisel et al., Biol Chem Hoppe Seyler. December 1988;369(12):1275-9);

[0085] - Peptide DEGEQPRPFPFP (Lv et al., Food Chemistry, Volume 141(3), 2013, Pages1645-1650);

[0086] - Peptide WEWLHYW (Charoenphun et al., Eur Food Res Technol 236, 57–63 (2013));

[0087] - Peptide DGDDGEAGKIG (Chen et al., Journal of Functional Foods, Volume 6, 2014, Pages 575-584);

[0088] - Peptide GPAGPHGPPG (Guo et al., Food Chemistry, Volume 173, 2015, Pages 536-542);

[0089] - Peptide VLSGGTTMYASLYAG (Jung et al., Eur Food Res Technol 224, 763–767 (2007));

[0090] - Peptide TCH (Huang et al., Eur Food Res Technol 232, 281–287 (2011));

[0091] - The peptide VLGYIQIR (Hou et al., Food Chemistry, Volume 243, 2018, Pages 389-395); and

[0092] - Peptide DNLPNPEDNKNYQ (Choi et al., Food Sci Biotechnol 21, 1663–1667 (2012)).

[0093] According to a preferred embodiment, the peptide capable of inducing calcium phosphate nucleation is a peptide derived from statherin, more particularly a SNA15 analog, even more particularly a peptide selected from SNA15, SNS15 and SN11. Preferably, the peptide capable of inducing calcium phosphate nucleation is a SNA15 peptide.

[0094] The peptide capable of inducing calcium phosphate nucleation may contain a cysteine ​​residue at each end thereof. The cysteine ​​residue may be covalently linked to the amino acid sequence of the peptide directly or through a spacer (particularly a peptide or pseudopeptide spacer). Specifically, the spacer may be an amino acid or an amino acid sequence (particularly a dipeptide or tripeptide), particularly a β amino acid, more particularly a β-Ala amino acid. According to a preferred embodiment, before crosslinking and hydrogel formation, the peptide capable of inducing calcium phosphate nucleation can be introduced into the composite matrix of the present invention can have the formula CβA-DDDEEKFLRRIGRFG-βAC.

[0095] According to a particular embodiment, the amount of peptide capable of inducing calcium phosphate nucleation in the composite matrix according to the invention is between 99.9 and 0.1% (w / v). As mentioned above, according to a particular embodiment, for a composite matrix with a concentration between 3 and 5% (w / v) and a thiol: olefin ratio of 1:1, the matrix may specifically comprise 0.1 to 3% (w / v) of at least one biologically active peptide.

[0096] 3. Calcium phosphate

[0097] Composite matrices according to the present invention also include mineral phases comprising calcium phosphates. Illustrative examples include calcium phosphates in the form of apatite, tricalcium phosphate, dicalcium phosphate and mixtures thereof. These calcium phosphate sources can be used in any available crystalline form. In addition, derivatives, particularly carbonaceous derivatives of these calcium phosphate sources can also be used. According to a specific embodiment, the calcium phosphate is in the form of apatite, more particularly hydroxyapatite. In advantageous cases, this calcium phosphate source allows the osteogenic properties of the composite matrix to be enhanced.

[0098] According to a particular embodiment, the composite matrix according to the invention comprises between 0.1 and 50% (w / v) of calcium phosphate. According to a particular embodiment, the composite matrix according to the invention comprises between 0.1 and 50% (w / v) of hydroxyapatite. More specifically, the composite matrix may comprise between 0.2 and 20% (w / v), more particularly between 0.5 and 4% (w / v), in particular between 2 and 3% (w / v) of hydroxyapatite. According to a particular embodiment, the composite matrix comprises 2.5% (w / v) of hydroxyapatite.

[0099] According to another particular embodiment, the composite matrix according to the invention comprises between 1 and 3% (w / v), more particularly 2% (w / v), of hydroxyapatite.

[0100] 4. Illustrative Embodiments of Composite Matrices According to the Invention

[0101] In particular, the composite matrix according to the present invention may comprise an elastin-like peptide, at least one bioactive peptide and calcium phosphate.

[0102] According to one embodiment, the concentration of the composite matrix is ​​between 1 and 10% (w / v), in particular between 3 and 5% (w / v), by density.

[0103] According to another embodiment, the mercaptan:olefin molar ratio is between 3:1 and 1:3, more particularly between 2:1 and 1:2, more particularly this ratio is equal to 1:1.

[0104] According to a particular embodiment, the composite matrix comprises:

[0105] (i) Elastin-like peptides;

[0106] (ii) at least one adhesion peptide;

[0107] (iii) at least one peptide capable of inducing calcium phosphate nucleation; and

[0108] (iv) Calcium phosphate.

[0109] Components (i) to (iv) may be selected from the components described in Sections 1 to 3 above.

[0110] More specifically, the composite matrix according to the present invention may comprise:

[0111] (i) peptides derived from the elastin-like peptide ELPM80;

[0112] (ii) peptide IKVAV and peptide YIGSR;

[0113] (iii) peptide SNA15 or a peptide similar to SNA15; and

[0114] (iv) Hydroxyapatite.

[0115] Preferably, the composite matrix according to the present invention comprises:

[0116] (i) peptide ELPM80;

[0117] (ii) peptide IKVAV(spacer)PVGLIG(spacer)YIGSR;

[0118] (iii) peptide SNA15; and

[0119] (iv) Hydroxyapatite.

[0120] More preferably, the composite matrix according to the present invention comprises:

[0121] (i) peptide ELPM80;

[0122] (ii) Peptide IKVAV-GGG-PVGLIG-GGG-YIGSR;

[0123] (iii) peptide SNA15; and

[0124] (iv) Hydroxyapatite.

[0125] 5. Methods for preparing composite matrices

[0126] The composite matrix of the present invention can be made by mixing its various components and any other optional elements. The components of the composite matrix and the amounts of these components are selected to produce a composite matrix having physical and support properties suitable for the user's requirements.

[0127] The person skilled in the art is familiar with the crosslinking techniques used in the prior art for making a composite matrix by crosslinking. Thus, the composite matrix can be prepared by crosslinking under the action of a stimulus such as a change in temperature or pH, or by crosslinking using a crosslinker, in particular a photosensitive crosslinker (or photoinitiator). As an illustrative example, mention may be made of the induction of photopolymerization using a photoinitiator such as the compound Irgacure 2959, which is used in particular at a density of 0.5% (w / v) in the mixture and activated by UV-visible light (λ=305-405 nm, in particular 305 nm) for 5 to 12 minutes, more particularly 6 to 10 minutes, in particular about 8 minutes. In another alternative, the photoinitiator may be selected from lithium phenyl-2,4,6-trimethylbenzoylphosphonate (LAP) and riboflavin. The concentration of LAP in the mixture may vary between 0.005% and 0.5% (w / v), and its photoinitiation may be triggered at a wavelength of 365 to 475 nm for 5 to 12 minutes, more particularly 6 to 10 minutes, especially about 8 minutes.

[0128] Advantageously, the skilled person can also refer to the preparation method described in the embodiments of the present application, wherein the hydrogel is prepared by forming a frozen matrix. In an alternative embodiment, a matrix precursor solution containing various matrix components is frozen to form a water crystal. When a cross-linking agent (i.e., a component carrying a thiol and alkenyl moiety) surrounds the water crystal, and when the solution is subjected to UV radiation, the olefin and thiol moieties of the various components of the mixture react at the interface of the crystal. When the solution thaws, the space occupied by the water crystal becomes a pore in the matrix. A freeze-drying step may be performed after this step. For example, after cross-linking, the matrix can be rehydrated, particularly for 24 hours, and freeze-dried under vacuum after deep freezing, thereby sublimating the ice without melting it, and generating new pores. The combination of these two techniques has the advantage of being able to form a wide distribution of pore sizes, allowing colonization of different cell types that can be used to induce angiogenesis, neural distribution, and osteogenesis.

[0129] Thus, according to a particular embodiment of the method of the invention, the freezing step is carried out at a temperature between 0 and -80°C, more particularly at a temperature of about -20°C, for at least 2 h, in particular for about 24 h. The matrix precursor can then be subjected to UV radiation suitable for inducing photopolymerization, in particular for about 5 to 12 minutes, more particularly for about 6 to 10 minutes, in particular for about 8 minutes. After crosslinking, and according to a particular embodiment, a rehydration step can be carried out, in particular for at least 2 h, in particular for about 24 h. This rehydration step can be followed by a deep freezing step at about -80°C for at least 1 h, in particular for about 24 h, followed by a freeze drying step lasting about 24 to 48 h.

[0130] As described above, these steps enable the formation of a composite matrix comprising pores having a broad, controllable pore size distribution. In particular, the composite matrix according to the present invention may have macropores having an average size greater than 100 μm.

[0131] 6. Use of the composite matrix according to the invention

[0132] Advantageously, the performance of the composite matrix can be very finely defined. In addition, the composite matrix according to the present invention is biodegradable and has a porous structure suitable for colonization by various cell types that can be used to induce angiogenesis, innervation and osteogenesis. The inventors can also prove that the composite matrix according to the present invention does not have cytotoxicity. Therefore, it brings together all the favorable properties that can be used to develop an instrument that is suitable for tissue regeneration.

[0133] Therefore, the composite matrix according to the present invention is able to efficiently support the in vitro culture of different cell types. Therefore, in a specific embodiment, the present invention relates to a new three-dimensional support, which can be used as a host for various cells of interest (especially neurons, bone or endothelial cells) for bone regeneration in vitro. Therefore, the present invention provides a particularly advantageous 3D cell culture system for those skilled in the art, allowing cells to develop in a favorable environment and also studying the interaction between different cell types. This parameter is important for studying regeneration phenomena that may require complex dialogues between different cell types. The carrier of the present invention is particularly useful for accommodating osteoblasts and endothelial cells and studying angiogenesis, osteogenesis and innervation in an in vitro cell culture method, including culturing cells in a carrier as defined above. The use of the support according to the present invention can also include adding agents to the culture, such as growth factors or any other agents (candidate agents) that have or may have biological effects, to determine their effects on one or more parameters and cell responses, such as cell growth, quiescent induction, cell death, secretion of proteins or other molecules or ions (especially calcium or potassium ions) or expression of certain genes.

[0134] According to another aspect, the composite matrix of the present invention is used for therapeutic methods, in particular as an implant. Specifically, the composite matrix is ​​used for regenerative medicine therapeutic methods. Specifically, it can be used to stimulate the nerve distribution of tissues, in particular bone tissues, and is particularly suitable for bone engineering. Advantageously, the composite matrix according to the present invention promotes nerve distribution, especially in a regenerative environment. More specifically, the composite matrix according to the present invention can be advantageously used to recruit and stimulate the sensory nervous system, more particularly to promote bone regeneration. The composite matrix according to the present invention can also be used to optimize or restore the vascularization and nerve distribution of tissues.

[0135] According to another embodiment, the composite matrix according to the invention is used to repair complex lesions showing vascular and neural damage.

[0136] Furthermore, the composite matrix according to the invention can also be used to regenerate the interface with the peripheral nervous system and to control bone development and repair.

[0137] According to another embodiment, the composite matrix can be used as a cell therapy medium. Therefore, the composite matrix as defined above can be used in advance to colonize the cells of interest in the treatment, for example, using stem cells, particularly induced stem cells in the pedigree of interest, hematopoietic stem cells, mesenchymal stromal stem cells derived from bone marrow or adipose tissue, neural stem cells or a mixture of cells of different pedigrees. Such composite matrix can be used for cell or tissue regeneration methods of treatment.

[0138] The composite matrix according to the present invention can also be used to modify implant systems and improve their biocompatibility and integration. Description of the Drawings

[0139] Figure 1 : Fluorescence scattering and pore size quantification of the hydrated matrix. A) Pore size quantification of ELPM80 + hydrated hydrogel YIGSR. N = 2 - 5 hydrogels (502 < pores < 2100), Kruskal - Wallis; Dunn's post - hoc test; p < 0.001. C) Pore sizes of ELPM80 + YIGSR hydrogels were classified as micropores (required for angiogenesis and innervation) and macropores (required for bone formation).

[0140] Figure 2 : Quantification of blood vessels and nerve structures formed within the hydrogel structures of the composition IKVAV + YIGSR and its scrambled version VKAIV + GYSRI. Each implantation is represented by a dot, and the mean is represented by a bar (n = 5 - 6). Note the high variability observed within the same group, confirming the heterogeneous cell colonization within the hydrogel structure. No statistical differences were detected.

[0141] Figure 3 : Matrix production steps: (1) Prepare the matrix precursor solution, freeze it at - 20 °C for 24 hours, then (2) cross - link under UV light. (3) Hydrate the frozen gel for 24 hours, then (4) freeze - dry.

[0142] Figure 4 : Quantification of the structure and pore size of matrices dehydrated to 4% (w / w) with 0% or 5% (w / v) HA. Pore sizes were quantified using ImageJ. Data are shown as ± SD, 10 < n < 32, and statistical differences are indicated by p < 0.001 (ANOVA and post - hoc Bonferroni test).

[0143] Figure 5 : Structure and pore size of dehydrated matrices produced using different final mass concentrations (% w / v) and different HA concentrations (% w / v) at an 8 - min cross - link time. Pore size quantification. Data are presented as mean ± SD, 7 < n < 26, and no statistical differences were observed (ANOVA and Bonferroni test as post - hoc test or Mann - Whitney test).

[0144] Figure 6 : Internal porosity of matrices hydrated at 3% (w / v) and 4% (w / w) with different HA concentrations. (B) Pore sizes were quantified using ImageJ. Data are presented as ± SD, 21 < n < 65, and statistical differences are indicated by p < 0.05 and p<0.001 (ANOVA and Bonferroni post hoc test) indicated. Scale bar: 100 μm.

[0145] Figure 7 : Mineralization potential of 3% w / v matrices without HA or containing 1%, 2%, and 2.5% w / v HA implanted subcutaneously in mice for 2 and 4 weeks. MicroCT acquisitions were quantified using MicroView software at day 0 (day of implantation), 2 weeks, and 4 weeks. Note that the volume of mineralized tissue increased over time and that matrices containing 2% and 2.5% w / v HA produced higher volumes of mineralized tissue than matrices without HA and containing 1% w / v HA. Data are expressed as mean ± SD, n = 4-5 mice per group, and statistical differences were determined by p<0.05 and p < 0.01 (ANOVA and Bonferroni post hoc test) indicated.

[0146] Figure 8 : Scanning electron microscopy coupled to EDX analysis of ELP matrix + IKVAV / YIGSR peptide with or without peptide SNA 15. ELP matrix + IKVAV / YIGSR peptide containing 0, 1, 2 and 2.5% w / v HA and with or without peptide SNA 15 was lyophilized and cut in half. The interior of the cut matrix was analyzed. The signals in the form of white dots correspond to calcium particles constituting hydroxyapatite. The scale bar shown in the figure corresponds to 2 mm.

[0147] Fig. 9 : Longitudinal micro-CT monitoring of matrix mineralization. Representative micro-CT images of subcutaneously implanted matrices without HA or with 1%, 2%, and 2.5% (w / v) HA at 0, 15, and 30 days after implantation. The mineral volume / total volume ratio (MV / TV) was measured from three-dimensional micro-CT images reconstructed using Microview® software. ANOVA statistical test followed by Bonferroni post hoc test was performed. p<0.05 and p<0.01.

[0148] Fig.10 : Micro-CT monitoring of mineralization of subcutaneously implanted ELP matrices containing 2% (w / v) HA using MicroView® software.

[0149] Fig.11: Histological analysis of the heterotopically implanted matrices stained with Masson's trichrome. Matrices containing 0%, 1%, 2% and 2.5% HA were implanted subcutaneously and stained with Masson's trichrome. Quantitative analysis of the osteoid tissue formed (15 < n < 23 per sample) was performed using the Kruskal-Wallis multiple comparison test, p <0.01 and p <0.001.

[0150] Fig.12 : Immunostaining of the vascular network and nerve structures in the composite matrix containing 2% HA at 0, 3, 7, 15 and 30 days after implantation at the ectopic site. (A) Quantification of the surface area occupied by blood vessels relative to the surface area of the matrix x 1000. (B) Quantification of the surface area occupied by nerve structures relative to the surface area of the matrix x 1000. Quantitative analysis using the Kruskal-Wallis multiple comparison test.

[0151] Fig.13 : Micro-CT analysis of the mineralization induced by the composite matrix in a rat femoral condyle bone lesion model. (A) Micro-CT images representing the bone lesions at 7, 15, 30 and 60 days after implantation and according to groups: the lesion left a cavity filled with the ELP matrix containing 2% HA and the positive control Collapat®. (B) For the three groups (cavity, ELP, Collapat®) and all implantation times (D7, D15, D30 and D60), the ratio of mineral volume / total volume (MV / TV) was measured from the three-dimensional micro-CT images reconstructed using Microview® software. Quantitative analysis of the mineralization was performed using the Kruskal-Wallis multiple comparison test, p <0.1, ns = not significant.

[0152] Fig.14 : Tissue sections of the lesions in the femoral condyles filled with the ELP matrix / peptide containing 2% HA. At 7 days after implantation, the bone lesions filled with the composite matrix were stained with Masson's trichrome. The area corresponding to the lesion was demarcated by a black dotted circle.

[0153] Fig.15 : Matrix mineralization in the mandibular bone lesion model. 3D micro-CT images show the reconstruction of the mandibular bone defect in the presence of the composite matrix.

[0154] Example

[0155] Example 1: Preparation of hydrogels with improved properties

[0156] The inventors' team recently evaluated a biomaterial that takes into account the importance of vascularization and innervation and the bone regeneration process (Paiva dos Santos et al., Acta Biomater. 2019, 99, 154). The aim of this work was to develop a cell-free, growth factor-free hydrogel that promotes angiogenesis and innervation. Hydrogels containing ELPM40, polyethylene glycol (PEG) and different concentrations of the adhesive peptide IKVAV (25% w / w and 50% w / w) were prepared, characterized and evaluated. In vitro tests could show that the 50% IKVAV composition had a greater potential to support osteogenesis, angiogenesis and innervation. In vivo, after subcutaneous implantation in mice, this composition did not induce any inflammatory response and allowed the induction of a higher vascular density and nerve endings formation in the surrounding tissue. However, this previous study had some limitations. First, the porosity of the hydrogel was not sufficient to allow uniform colonization of cells in the implant. In addition, the hydrogel did not seem to degrade after implantation, probably because PEG is not completely biodegradable in the long term.

[0157] Therefore, the inventors attempted to improve the composition and structure of the hydrogel to enhance the uniformity of cell colonization and the biodegradability of the material.

[0158] Development of methods to induce increased porosity

[0159] First, the inventors sought the best way to induce porosity in the hydrogel matrix and enable it to be colonized by cells. These structures were analyzed by scanning electron microscopy (SEM).

[0160] State-of-the-art hydrogels composed of ELPM40 and PEG were prepared and their pore sizes were characterized.

[0161] The first method for inducing porosity, hereinafter referred to as "CryoUV", involves forming a frozen matrix. A matrix precursor solution is frozen to form crystals. When a cross-linking agent surrounds the crystals, and when the solution is subjected to UV radiation, the olefin and thiol moieties of the various components of the mixture react at the interface of the crystals. When the solution thaws, the spaces occupied by the crystals become pores in the matrix.

[0162] Another method used is based on the production of matrices using the CryoUV method followed by a freeze-drying step (hereinafter referred to as "CryoUV+Lyoph"). After cross-linking, the matrix is ​​rehydrated for 24 h and freeze-dried under vacuum after 24 h of deep freezing, thereby sublimating the ice without melting it, thus creating new pores. The combination of these two techniques has the advantage of being able to form a wide distribution of pore sizes, allowing the colonization of different cell types that can be used to induce angiogenesis, innervation and osteogenesis.

[0163] The inventors evaluated the external structure of the matrix using environmental SEM. CryoUV hydrogels were prepared and their water content was evaporated before SEM analysis to achieve SEM visualization. For the CryoUV+Lyoph method, freeze drying preserved the three-dimensional structure of the hydrogel. The results show that both methods can produce hydrogels with porous structures.

[0164] The inventors then explored the possibility of modifying the hydrogel composition to improve the above-mentioned colonization and biodegradability properties.

[0165] Production of peptide ELPM(olefin)-80

[0166] The previously described coded ELPM40 MW [(VPGVG)(VPGMG)(VPGVG) 2 ] 15 The plasmid ELPM40-pUC19 (Petitdemange et al., Biomacromolecules. 2017 Feb 13;18(2):544-550) was digested with restriction endonuclease BsmF1 to linearize it and then 5' dephosphorylated with Antarctic phosphatase. The amino acid sequence [(VPGVG)(VPGMG)(VPGVG)] was extracted from the plasmid pUC19 encoding ELPM20, which was also described above, by digestion with restriction enzymes BsmF1 and BtgZI. 2 ] 5The nucleotide sequence was used as an insertion sequence and introduced into the linearized plasmid ELP M40-pUC19 by ligation to obtain plasmids pUC19-ELPM60 and pUC19-ELPM80 encoding ELPM60 and ELPM80, respectively. Then, after digesting the plasmid pUC19-ELPM80 with restriction enzymes NdeI and BamHI, the sequence encoding ELPM80 was transferred to the expression vector pET44a, allowing ELPM80 to be expressed under IPTG induction. The article by Petitdemange et al. (Biomacromolecules. 2017 Feb 13;18(2):544-550) describes the peptide MX [VPGVGVPGMG (VPGVG) 2 ] 10 Construction of an expression vector for (ELPM40), its expression in E. coli, isolation from bacterial lysate, purification and characterization. These conditions were applied to the production and purification of ELPM80. 1H NMR and MALDI mass spectrometry confirmed the correct structure and molecular weight.

[0167] The olefin moiety was then added to the peptide ELPM80 by chemoselective thioalkylation of the methionine side chain of the peptide ELPM80 using allyl glycidyl ether, again according to the conditions described in Petitdemage 2017, yielding the peptide ELPM(olefin)-80, which was later named ELPMa-80. The structure of the resulting olefinated peptide was confirmed by 1H NMR.

[0168] Production and characterization of composite matrices containing ELPM80

[0169] In order to improve the hydrogel composition, the inventors replaced the ELPM40 contained in the prior art composition with the elastin-like peptide ELPM80. Incidentally, the adhesion peptide YIGSR was also introduced into the hydrogel composition. Its scrambled version GYSRI was used as a control. The resulting hydrogel composition is shown in Table 1.

[0170]

[0171] Table 1: Hydrogel compositions containing ELPM80 and adhesion peptide YIGSR

[0172] Diffusion of FITC-dextran 500 kDa in the matrix structure and assessment of fluorescence in the core material by confocal microscopy were used to quantify pore size and porosity using ImageJ. The lowest measured pore size was 2.16 µm for both the CryoUV and CryoUV+Lyoph methods, the highest measured pore size was 382.5 µm for the CryoUV method, and 523.5 µm for the CryoUV+Lyoph method, indicating that the latter produces larger pores ( Figure 1 ).

[0173] To allow for angiogenesis, innervation, and bone formation, a very wide range of pores is required. Data from the literature suggest that the optimal size is 0.005 to 0.3 μm for innervation, 5 to 15 μm for fibroblast growth, 50 to 400 μm for rapid vascularization, and 100 to 400 μm for bone regeneration. Considering the pore size for inducing bone formation, we evaluated the pore frequency according to size, expressing it as micropores (less than 100 µm) and macropores (greater than 100µm). In general, macropores were more common when the samples had been freeze-dried compared to the CryoUV method ( Figure 1 ), which satisfies angiogenesis, innervation and bone regeneration.

[0174] Based on the previous section, the CryoUV+Lyoph method was standardized to ensure (i) high porosity while taking into account (ii) large pore size criteria to meet the prerequisites for cellular colonization of different cells to achieve angiogenesis, innervation and osteogenesis; iii) compositional modifications were made to produce an all-natural polymer material in order to promote matrix degradation, which means that PEG-free matrices can be produced while maintaining equimolar concentrations of olefins / thiols; iv) ELPM40 was replaced by ELPM80. The inventors implanted the IKVAV+YIGSR composition and its scrambled version subcutaneously in mice to evaluate the angiogenesis and innervation potential in vivo. After 4 weeks of implantation, the samples were harvested and histologically analyzed by hematoxylin-eosin (HE) staining to evaluate tissue architecture, cellular colonization and sustained inflammation. For angiogenesis potential, CD31 immunohistochemistry (IHC) was performed, and for innervation potential, β3 tubulin IHC was used. No sustained inflammatory signs were observed for both compositions, and nerves and blood vessels were seen within the hydrogel. However, heterogeneous cell colonization did occur, indicating the need to optimize and standardize material production. Quantification of vascular and neural density also confirmed these observations, showing great variability within the same group ( Figure 2 ).

[0175] Based on the data summarized above, modifications seemed necessary to improve the function of the hydrogels in vivo. Given the limited reproducibility of the hydrogels and the resulting cell colonization, the inventors decided to optimize the matrix production protocol and modify the composition in order to incorporate osteogenic potential in a new generation of materials. As described above, using hydrogels based on ELPs and adhesive peptides, the inventors have shown that the hydrogels are able to induce angiogenesis and innervation around the implant site.

[0176] To improve the biofunctionality, the inventors considered other biomimetic peptides to enhance the recruitment of neural and vascular cells, matrix degradation, cell colonization and mineral content retention: (i) the basic adhesion peptides CβA-IKVAV-βAC and CβA-YIGSR-βAC were replaced with the sequence CβA-IKVAV-GGG-PVGLIG-GGG-YIGSR-βAC, where the same cross-linking chemistry strategy was retained: sulfhydryl groups were present on the flanking cysteines, enabling cross-linking with olefins grafted on ELPM80. The inventors also used a control peptide in which the scrambled versions VKAIV and GYSRI replaced their original sequences IKVAV and YIGSR, respectively. The sequence PVGLIG was retained in this control peptide. Three glycines were used as spacers between the functional units, and (ii) PVGLIG, a target degradation site for matrix metalloproteinases 2 and 9, was included between the two adhesion sequences. Therefore, once cleaved, each adhesion sequence would still be attached to the matrix and available for cell attachment. In addition, this sequence would trigger matrix degradation, thereby facilitating cell colonization. (ii) The peptide SNA15 (CβA-DDDEEKFLRRIGRFG-βAC), a calcium phosphate nucleating unit derived from statherin, was used to retain the hydroxyapatite particles and ensure their uniform distribution. Therefore, (iii) hydroxyapatite (HA), corresponding to the synthetic bone mineral inclusions, was included in the material composition to provide a biochemical signal for osteoconductive properties. The inventors' research group has synthesized and characterized them, and they have rod-shaped HA crystals of 50-100 nm, forming aggregates with an average diameter of 3.26±0.62 μm. Using the CryoUV+Lyoph method, the inventors standardized the incubation time in the matrix production protocol ( Figure 3 ).

[0177] Given the importance of porosity and pore size, the next step in the characterization process was to optimize the matrix based on several factors: cross-linking time, final mass concentration, and HA concentration. Photopolymerization was induced using the photoinitiator Irgacure 2959, which was specifically used at a density of 0.5% (w / v) in the mixture and activated by UV-visible light at 305 nm. The cross-linking time was first evaluated because it has a direct impact on the generation of the matrix. Matrices composed of ELPM80, biomimetic peptides containing the sequences of IKVAV, PVGLIG, and YIGSR, SNA15, and with or without HA at 4% (w / v) were prepared (Table 4) and cross-linked for 5 min, 8 min, and 15 min. Images from the matrices were obtained using scanning electron microscopy and the pore size ( Figure 4 ).

[0178]

[0179] Table 4. Matrix composition and concentrations of all components

[0180] The biomimetic peptide consisted of a single peptide containing the units IKVAV, PVGLIG, and YIGSR. The scrambled version consisted of VKAIV and GYSRI without affecting the sequence PVGLIG.

[0181] The results obtained show that the shorter the cross-linking time (5 min), the larger the pores. In fact, in the case of a cross-linking time of 15 min, very few pores were observed. Without wishing to be bound by any theory, the inventors assume that the longer the cross-linking time, the more likely the frozen matrix will begin to thaw. This will result in a harder matrix due to a higher cross-linking rate and smaller pores due to thawing. In fact, this can explain why very few pores can be observed in the case of a cross-linking time of 15 min. In general, in matrices without HA, the pore size varies with the change of cross-linking time, but in the case of a 5% (w / v) HA matrix, there is no difference in pore size. This shows that HA interferes with the formation of pores, regardless of the cross-linking time. Taking into account the pore size in matrices with and without HA and the fact that the matrix is ​​dehydrated, the inventors decided to standardize the cross-linking time to 8 minutes for subsequent experiments.

[0182] Next, the inventors evaluated the effect of the final matrix concentration on the pore size. They prepared 2% (w / v), 3% (w / v), and 4% (w / v) matrices with different HA concentrations and analyzed their microstructures ( Figure 5 ).

[0183] The 3% (w / v) matrix tended to maintain its structure depending on the HA concentration, while the 2% (w / v) and 4% (w / v) matrices had a powdery structure that could reduce reproducibility. SEM analysis confirmed the external porosity of the dehydrated matrices produced using an 8 min cross-linking time and showed that the packing density of the network increased proportionally with the matrix concentration. The 4% (w / v) matrix appeared to contain more pores but with smaller diameters, while the 2% (w / v) and 3% (w / v) matrices appeared to contain fewer pores but with larger sizes. The pore size of the dehydrated matrices with the same HA concentration did not change with the final concentration. Similarly, the HA content appeared to interfere with the pore size in matrices with the same final concentration, but this trend did not appear to be statistically significant.

[0184] To confirm these results and assess the internal porosity, the inventors quantified the pore size in the hydrated matrix by cutting the hydrated matrix in the middle and preparing tissue sections by cryostat. Figure 6 showed that, in the 3% (w / v) matrix, the 5% HA matrix had smaller pore sizes than matrices containing 0% and 2.5% HA. Furthermore, when comparing the 3% (w / v) and 4% (w / v) matrices, the 3% (w / v) matrices with 0%, 2.5% HA, and 5% HA had significantly larger pores than the 4% (w / v) matrix at the same HA concentration. Importantly, in the 3% (w / v) matrix, there was no difference in pore size between matrices without HA and those containing 2.5% (w / v) HA, and the pore size was greater than 100 μm, which is the minimum pore size described in the literature to be sufficient for osteogenesis. Since then, work has focused on 3% (w / v) matrices containing up to 2.5% (w / v) HA.

[0185] Next, the inventors evaluated the bulk porosity of matrices without HA and with 2.5% (w / v) HA after rehydration. They used the method described by Ma and Zang based on the total density and skeleton density of the fiber matrix (Ma and Zhang, J. Biomed. Mater. Res. 1999, 46, 60). The skeleton density was taken as the density of the polymer and HA. There was no difference in porosity between matrices without HA and with 2.5% w / v HA. The porosity of the matrix without HA was 98.9 ± 0.26%, compared to 98.9 ± 0.49% for the 2.5% w / v HA matrix. These results indicate that the presence of HA does not interfere with the bulk porosity of the hydrated matrix.

[0186] The retention of HA in the matrix structure was then investigated by thermogravimetric analysis (TGA). The HA content retained in the matrix structure reached a plateau at 2.5% (w / v). Therefore, the inventors decided to use a maximum final HA concentration of 2.5% (w / v) for the rest of the experiments, but did not exclude the possibility of using matrices containing 1% or 2% HA, given the results obtained at 2.5%.

[0187] The inventors then analyzed the distribution of HA on the surface and inside the matrix by EDX. SEM images confirmed the surface and internal porosity of the matrix with or without HA. EDX analysis is an X-ray technique used to identify the elemental composition of a material; in this case, calcium inclusions are visible in the form of white spots. The experiments can show that hydroxyapatite is uniformly distributed on the surface and in the matrix.

[0188] In parallel, biological assessments were performed to analyze cell survival and distribution in the matrix. Rat primary endothelial cells (EC)-RFP and bone marrow-derived mesenchymal stem cells (BMSC) were co-cultured with the matrix and observed by confocal microscopy. The latter were acquired with a z-volume of 130 to 190 µm and analyzed using Imaris for 3D representation. After 7 days of co-culture, EC-RFP were observed in the periphery and in the matrix, indicating that the matrix provided support for cell culture. To evaluate whether cells colonized the matrix core, they were cut in the middle and histological sections were prepared using a cryostat. The core of the samples was counterstained with DAPI (40,60-diamidino-2-phenylindole) and images were captured to detect RFP and DAPI to evaluate cell colonization in the matrix core. For the matrix without HA, no RFP or DAPI staining was observed in the core of the matrix, but only at its periphery. On the other hand, RFP+ cells were evenly distributed within the matrix containing 2.5% HA.

[0189] After extensive matrix characterization, the inventors implanted 3% w / v matrices without HA or with 1%, 2%, and 2.5% w / v HA subcutaneously into mice. The inventors then monitored implantation using microCT at the day of implantation (Day 0), 2 weeks (2W), and 4 weeks (4W) to assess the mineralization potential of the matrix. MicroCT confirmed the formation of ectopic mineralized tissue within 2 and 4 weeks of implantation ( Figure 7). Upon quantification, the volume of mineralized new tissue formed in matrices containing 1%, 2%, and 2.5% w / v HA increased over time. Matrices containing 2% and 2.5% w / v HA did not differ in the induction of mineralized new tissue formed after 2 or 4 weeks of implantation. After 2 weeks, matrices containing 2% and 2.5% produced a greater volume of mineralized tissue than matrices containing 1% w / v HA. When comparing the volume of mineralized tissue produced by matrices containing 1% and 2% w / v HA, p=0.059 was obtained. Matrices without HA were not visible and did not produce significant mineralized tissue over time. In some animals, a small amount of mineralized tissue was observed at 2 weeks, but it was undetectable by week 4 and was presumably resorbed. These data suggest that matrices containing 1-2.5% HA have the potential for ectopic mineralization, and that 2% and 2.5% w / v HA performed best after 2 weeks.

[0190] In summary, the inventors describe a novel acellular and growth factor-free matrix composite that is able to induce the formation of ectopic mineralized tissue in mice. This matrix consists of ELPM80 and is functionalized with biomimetic peptides responsible for the recruitment of neural and vascular cells, stimulation of cell colonization, and retention of HA. The functionalized matrix has osteoinductive properties in combination with 1-2.5% (w / v) HA.

[0191] Example 2: Evidence for the relevance of peptide SNA15 in the retention and distribution of hydroxyapatite particles

[0192] As described above, the inventors prepared a composite matrix whose organic part consisted of ELPM80-olefin, biomimetic peptides containing adhesion sequences IKVAV, YIGSR, proteolytic cleavage motif PVGLIG and calcium nucleating peptide SNA15, and whose inorganic phase consisted of hydroxyapatite microparticles.

[0193] The calcium phosphate nucleating peptide SNA15 having the sequence DDDEEKFLRRIGRFG is derived from the salivary protein statherin. A modified SNA15 peptide having the sequence CβA-DDDEEKFLRRIGRFG-βAC was used.

[0194] Composite matrices with or without the peptide SNA15 were prepared using the same ELP matrix concentration and varying HA concentrations from 0% to 2.5%.

[0195] Energy dispersive X-ray (EDX) analysis was performed to determine the surface elemental composition of the material, more specifically the element calcium (in Figure 8 ). As can be seen, the matrix without HA contains almost no calcium. As expected, the more HA particles added to the matrix, the more the signal increases. This phenomenon is even more pronounced when the gel contains the peptide SNA15.

[0196] Quantitative analysis showed that the atomic percentage of calcium in the matrix containing SNA15 was greater than that in the matrix without SNA15: 8 times the calcium in the 1% HA+SNA15 matrix, 8.9 times the calcium in the 2% HA+SNAP15 matrix, and 12.6 times the calcium in the 2.5% HA+SNA5 matrix compared to the matrix without peptide SNA15.

[0197] It can be concluded that peptide SNA15 can significantly improve the retention of calcium phosphate particles, since in its presence calcium phosphate particles were 8 to 12.6 times more abundant.

[0198] Example 3: In vivo evaluation of ELP-based composite matrices in ectopic sites and bone lesions

[0199] I. Ectopic Implantation of ELP Matrices Supplemented with Different Concentrations of Hydroxyapatite

[0200] ELP and peptide matrices containing different concentrations of HA particles were implanted subcutaneously to select the matrix with the best mineralization, vascularization, and innervation capabilities. The four matrices differed only in their HA content (0%, 1%, 2%, and 2.5% particles).

[0201] I.1. Study of the mineralization potential of the composite matrix

[0202] Mineralization of the matrix implanted into the subcutaneous site was monitored by X-ray micro-tomography (micro-CT) immediately after matrix implantation (D0) and then after 15 and 30 days (D15 and D30). Fig. 9 ). At day 0, no mineralization was observed in the 0%, 1%, and 2% HA implants, whereas very little mineralization was observed in the 2.5% HA matrix ( Figure 8 ). These results indicate that HA particles at the concentrations studied are only slightly visible using the micro-CT technique.

[0203] Ectopic mineralized tissue was formed in matrices containing HA particles after 15 and 30 days of implantation. The volume of mineralized tissue formed in these composite matrices increased over time ( Figure 8 However, no mineralization was detected after implantation of matrices without HA, indicating the importance of these particles in the mineralization process. After 1 month of implantation (D30), matrices containing 1% HA induced an increase in mineral volume of 21 ± 10%, matrices containing 2% HA 42 ± 7%, and matrices containing 2.5% particles 37 ± 5%. After 30 days of implantation, we did not measure any significant differences in the amount of mineralized tissue formed between matrices containing 2% and 2.5% HA. Mineralization of the 2% HA matrices was shown in Fig.10 middle.

[0204] I.2. Study on the osteoinductive properties of composite matrix

[0205] At 4 weeks post-implantation, matrices were excised, embedded in paraffin, and analyzed histologically using Masson's trichrome staining to assess tissue architecture, cellular colonization, inflammation, and osteoid tissue formation.

[0206] Histological sections of the material in relation to the surrounding epidermis, fat and muscle tissue showed that, one month after implantation, almost no fibrosis occurred around the ELP matrix, regardless of the formulation. This suggests that the matrix induced little inflammation and was not rejected. These results are consistent with the biocompatibility demonstrated in vitro. On these sections, we can again see the presence of a lamellar structure and pores.

[0207] The presence of cell nuclei within the implanted matrices was also observed, indicating that the cells had been able to penetrate these matrices.

[0208] Since the tissue and matrix had not yet been decalcified, some of the highly mineralized areas were damaged during microtome cutting. However, the presence of mineralization in the form of dark purple crystals can be noted. Osteoid tissue can also be seen at the periphery and within the matrix.

[0209] The amount of newly formed osteoid tissue ( Fig.11 ) increased significantly as the amount of HA in the matrix increased from 0% to 2%. In contrast, the values ​​measured in matrices containing 2.5% mineral fraction were not significantly different from those containing 2%. Therefore, matrices containing 2% HA particles appear to be a favorable formulation for stimulating mineralization and osteoinduction processes.

[0210] I.3. Studies on the angiogenic and innervating potential of the ELP matrix

[0211] The formation of vascular and neural structures was visualized by immunostaining for vascular markers (endothelial mucin) and neuronal markers (β III tubulin). During this study, histological sections of matrices were obtained at 0, 3, 7, 15 days, and 1 month after implantation to determine the kinetics of the formation of these structures.

[0212] Regarding the formation of vascular structures on day 0, no blood vessels were observed in the matrix at about 3 to 4 hours after implantation. Three days after implantation, blood vessels appeared mainly at the periphery of the matrix, and then their infiltration was observed on day 7. After 15 days of implantation, blood vessels were present both at the periphery and inside the matrix. By day 30, the vascular network within the matrix became denser.

[0213] These observations were confirmed by the quantification of intrastromal blood vessels studied ( Figure 1 éA). At 1 month post-implantation, vascularization increased by approximately 10% in all matrices, regardless of HA concentration. Significant differences were only observed between matrices without HA (0%) and those containing 1% HA.

[0214] The ability of the matrix to stimulate innervation was also demonstrated by the presence of nerves at the periphery of the material, especially in the early stages after implantation. During bone regeneration, neural structures are the first to appear, even in the early stages after bone injury. This explains the presence of several nerve fibers visible at the periphery of the composite matrix from day 3 of implantation. After 1 month, neural structures were still detectable at the periphery of the matrix, but their diameter seemed to have increased.

[0215] Quantitative results obtained by measuring the surface area occupied by neural structures located at the periphery of the matrix relative to the total surface area of ​​the matrix confirmed previous observations ( Fig.12 B). In terms of formulation, it appears that the composite matrix containing 1% HA significantly stimulated the formation of neural structures one month after implantation. This was particularly evident when these results were compared with those obtained using matrices without HA or supplemented with 2.5% HA.

[0216] Since the measured density of nerves or blood vessels can vary depending on the position and / or angle of the tissue section, we also used a technique that allows visualization of the entire tissue in three dimensions without cutting the sample after immunofluorescence labeling of the neuronal network. This technique allows observation of the autofluorescence of the matrix and the presence of a network of neural structures expressing β III tubulin in three dimensions. In particular, a strong presence of neural structures close to the matrix can be seen. Incidentally, the vascular network appears to be evenly distributed.

[0217] I.4. Study of inflammatory response after subcutaneous implantation of composite matrix

[0218] A moderate inflammatory response is necessary for tissue regeneration and vascularization. On the other hand, a response from the immune system that is too strong can lead to rejection of the implant.

[0219] In the case of composite matrices, histological analysis using Masson's trichrome (MT) staining did not reveal any inflammatory fibrotic capsule surrounding the implants, regardless of their composition.

[0220] To confirm these data, we performed immunolabeling of immune cell populations. As an inflammatory marker, we used CD11b, expressed by the entire myeloid cell lineage (monocytes, macrophages, neutrophils), and CD45, a more specific marker for lymphocytes. We found that, a few hours after implantation, immune cells were recruited to the periphery of the matrix. These cells were still detected up to day 7 after implantation. Thereafter, after 3 and 6 months, immune cells were present exclusively in the interior of the matrix. They are probably macrophages that could play a role in matrix degradation.

[0221] I.5. Future in vivo studies of composite matrices

[0222] To determine the longevity of the matrices, subcutaneous implantations were performed and their future was monitored for up to 6 months after implantation.

[0223] Immediately after implantation (D0), the composite matrix containing 2% HA particles was clearly visible (reddish) and blue HA crystals could be distinguished. After 1 month of implantation, the free space left by the pores was filled as a result of cellular colonization. Several nuclei within the matrix could be identified. After 3 months of implantation, the structure of the matrix was no longer visible, probably due to its degradation by the immune system. It was possible to note the presence of a large number of cellular components and extracellular matrix filling the space previously occupied by the composite. Similar results were observed after 6 months, but there was an increase in mineralization throughout the area previously occupied by the composite matrix.

[0224] In summary of these studies performed in ectopic sites, matrices developed from ELP, peptides IKVAV / YIGSR and SNA15 showed their ability to promote angiogenesis and innervation. Supplementation of matrices with HA endowed them with osteoinductive properties as they were subsequently able to form mineralized tissue and osteoid tissue.

[0225] In conclusion, the composite matrix containing 2% HA was selected as the implant in the bone site because it performed best in terms of bone neogenesis, angiogenesis, and generation of neural structures.

[0226] II. Implantation of the Composite Matrix into the Bone Site

[0227] The regenerative capacity of composite matrices containing 2% HA was evaluated in rat models of femoral condylar defect and mandibular defect.

[0228] II.1. Implantation in the femoral condyle of rats

[0229] A circular defect with a diameter of 3 mm was created in the rat femoral condyle. Three conditions were tested: an unfilled defect corresponding to a negative control, a defect filled with our composite matrix, and a defect filled with a commercially available Collapat® matrix used as a positive control.

[0230] Micro-CT analysis was performed at different times (7, 15, 30, and 60 days) after implantation to monitor the mineralization of the condylar defect. A 2D image of the femoral condyle reconstructed by 3D micro-CT is shown in Fig.13 In A, quantification of mineralized tissue volume relative to total volume (MV / TV) is shown in Fig.13 In B.

[0231] Micro-CT images revealed the formation of mineralized volumes in lesions filled with composite matrix and Collapat®, whereas less mineralization was detected in unfilled defects ( Fig.13A).

[0232] The results of quantitative analysis ( Fig.13 B) shows that the unfilled defect was partially mineralized and the MV / TV ratio did not increase significantly over time. At 7 days, the ratio was 8.6% ± 4.8%; it then increased to 10.3% ± 5.6% at 15 days, 14.7% ± 5.9% at 30 days, and 37.5% ± 3.0% at 60 days. However, we observed site fractures in some animals, which complicated the quantification of MV / TV. Our previous work showed that bone lesions with a diameter of 2.8 mm can repair naturally (Schlaubitz et al., 2014). In the present case, a lesion with a diameter of 3 mm was created, which may have weakened the lesion site and caused fracture, thereby delaying or altering the repair kinetics. However, micro-CT images revealed mineralization at the periphery of the lesion, which explains the high MV / TV ratio in the region of interest (ROI) ( Fig.13 B). In all cases, the images observed for the unfilled lesions differed from those obtained after composite matrix implantation.

[0233] Indeed, in this case, mineralization was observed to start at the inner edge of the lesion and to increase over time after implantation. Initially, mineralization was essentially peripheral and then progressed toward the interior of the lesion over time. After 60 days of implantation, it could be seen that the cortical part had been remodeled, in stark contrast to the unfilled defect ( Fig.13 A). Quantitative analysis showed that the MV / TV value increased significantly over time ( Fig.13 B). They were 8.0 ± 3.9% after 7 days of implantation, 15.6 ± 7.0% after 15 days, 28.8 ± 14.2% after 30 days, and 56.0 ± 6.9% after 60 days.

[0234] Using the control material, Collapat®, the MV / TV was 40.2 ± 9.4% from day 7 of implantation, which is much higher than the value measured using the ELP / peptide / HA composite matrix. This result was expected, as this commercial material contains a high content of calcium phosphate particles, which induces an X-ray signal ( Fig.13 A). No significant increase in mineralization was observed from D7 to D30. The MV / TV ratio showed little or no change, with a value of 67.3 ± 6.3% after 60 days.

[0235] Thus, if we compare the three conditions studied, we can observe that the amount of mineralized tissue measured between days 7 and 60 increases to 4.4 times in the unfilled defects, to 7.1 times with our composite matrix and to 1.7 times in the case of Collapat®.

[0236] The composite matrix-induced bone regeneration was then histologically analyzed.

[0237] At 7 days, 15 days, 1 month, and 2 months after implantation, the femurs were removed, decalcified, and tissue sections were obtained. These sections were then stained with Masson's trichrome ( Fig.14 ).

[0238] Observe the tissue sections of the lesion area. For the unfilled lesions, the defect borders were still clearly visible 7 days after surgery. After 15 days, the lesions were mainly filled with collagenous tissue. By the 30th day, the borders of the lesions were difficult to discern, and organized bone-like tissue appeared at the periphery.

[0239] Histological sections showed that the ELP / peptide / HA composite matrix was well integrated into the bone defect. There was no visible boundary between the lesion area and the material. The presence of a large number of cell nuclei within the matrix confirmed the cellular colonization. In addition, the absence of fibrosis was a sign of good biocompatibility of the matrix used. Quantification of the newly formed osteoid tissue showed an increase starting from day 15, with the maximum amount measured at day 30. However, by two months, the amount of osteoid tissue had decreased. Analysis of the histological sections showed that bone formation occurred from the periphery to the center of the defect, which confirmed the images observed by micro-CT ( Fig.13 A).

[0240] Regarding the Collapat® material, good osseointegration was also observed, as well as the formation of bone tissue from the periphery to the center of the defect. Quantification of the newly formed osteoid tissue also showed that the neogenesis reached a maximum after 30 days, which is comparable to the kinetics observed with our composite matrix.

[0241] To specifically visualize the presence of osteoblasts, immunolabeling for osteocalcin, a specific marker for bone tissue, was performed. The images showed that the unfilled lesions were almost devoid of osteoblasts at 7 and 15 days after surgery. After 30 days, a small number of osteoblasts were detected at the edges of the area defining the bone lesion.

[0242] In the case of the composite matrix and Collapat®, osteocalcin was detected as early as day 15, and its presence was confirmed at days 30 and 60, confirming the presence of osteoblasts in the neoplastic tissue.

[0243] To assess vascularization and innervation in condylar lesions, vascular (endothelial mucin, podocalyxin, and Meca32) and neural (β III tubulin) markers were analyzed using whole bone clearing. This analysis allowed visualization of the organization of vascular and neuronal networks in the initial injured area. Multiple labeling was used to facilitate visualization of thick samples, as was the case with whole bone (Kirst et al., 2020, Cell 180, 780-795.e25).

[0244] 2D sections of lesions filled with a composite matrix containing 2% HA were analyzed 30 days after implantation. Bone tissue appears green due to its autofluorescence, vascular networks appear blue-green, and neuronal extensions appear red. 2D images acquired at 15 and 30 days after implantation for each condition were also analyzed: unfilled lesions, lesions filled with a composite matrix or Collapat®.

[0245] In the lesions that had not yet filled, a vascular network had developed. It seemed to originate mainly from the peripheral muscle tissue. After 30 days, vascular and neural structures were detected within the injured area. However, histological analysis using TM staining showed that the injured area had filled with soft, disorganized, collagen-rich tissue.

[0246] For lesions filled with composite matrices, the formation of a vascular network throughout the matrix was observed as early as day 15.

[0247] In contrast, for defects filled with Collapat®, vascularization was mainly present at the periphery of the defect. Moreover, this vascularization was only visible from day 30 after implantation. Therefore, these qualitative results show that the Collapat® matrix is ​​not as effective as our composite matrix in promoting vascularization of the implant.

[0248] Regarding the innervation, although most of the fibers were present in the periosteum covering the cortical bone surface, a small number of fibers could be seen within the lesion for defects that were either unfilled or filled with composite matrix. In contrast, no nerve fibers were detected when the condylar defect was filled with Collapat®.

[0249] II. Implantation of composite matrix in mandibular defects

[0250] In order to evaluate the use of materials developed for craniofacial bone reconstruction, a mandibular defect model was chosen. Among the skull bones, only two are movable: the hyoid bone and the mandible. The mandible has the advantage of being larger and more accessible.

[0251] Compared to the calvaria defect classically used to test bone repair materials, the mandibular defect also offers the advantage of being subjected to high mechanical stresses. But these mechanical stresses are necessary for effective bone repair. In the mandible, the stresses are essentially associated with chewing. Therefore, this mandibular lesion model was chosen to test bone repair materials because it is more physiologically realistic than the calvaria defect.

[0252] To validate this model, preliminary experiments were performed. A circular defect with a diameter of 3 mm was created and its repair was monitored using micro-CT. After 3 months, no bone repair was observed, indicating that the defect had indeed reached a critical size.

[0253] Initial micro-CT observations were performed at different times (7, 15, and 30 days) after implantation to monitor the mineralization of the mandibular defect. 3D images of the mandibular bone filled with the composite matrix reconstructed by micro-CT are shown in Fig.15 middle.

[0254] Partial remodeling of the defect periphery was observed on day 30. Quantification of MV / TV was comparable at day 7, 0.037 ± 0.010, and at day 15, 0.040 ± 0.018. On day 30, an increase in the MV / TV ratio was measured (0.094 ± 0.049).

[0255] Tissue sections obtained 15 days after composite matrix implantation were analyzed by TM staining.

[0256] Interestingly, an area was observed at the junction of bone and matrix that highlighted the presence of new bone tissue, along with the presence of osteoblastic border cells, small boxes with osteocytes within what appeared to be layered bone structures. Blood vessels were also seen in the new tissue.

[0257] Furthermore, if one considers tissue remodeling from the periphery to the center of the lesion, it is important to note tissue invasion, which is accompanied by vascularization and the formation of bone tissue in contact with the matrix, thus confirming their osteoconductive potential.

[0258] Example 4: Conclusions of in vivo studies

[0259] In summary, various composite materials were tested in vivo in small animals at both ectopic and orthotopic sites.

[0260] All tested matrices integrated well with the surrounding tissues without causing any severe inflammatory reactions. It has also been shown that matrices containing HA induce mineralization. Vascular structures invaded the implants, demonstrating their angiogenic potential. The ability of the matrices to stimulate innervation was also demonstrated by the presence of nerves at the periphery of the material, especially in the early stages after implantation.

[0261] A matrix containing 2% HA was chosen for its ability to promote mineralization and its angiogenic potential. It was implanted into condylar and mandibular defects.

[0262] Bone remodeling was improved following implantation of the composite matrix in condylar defects compared to unfilled defects. Organized bone structures expressing osteocalcin were identified in these hydrogels. An organized vascular network developed throughout the bone lesion, which was not the case with the Collapat® control material.

[0263] The results obtained in the mandibular defect model showed very satisfactory results for the osteoconductive and angiogenic properties of the composite matrix. Histological analysis showed that the material was well integrated. Bone and vascular structures were found as early as 15 days after implantation.

[0264] These results therefore demonstrate the therapeutic value of the composite matrices of the present invention.

Claims

1. A composite material comprising: at least one elastin-like peptide, at least one bioactive peptide, A peptide capable of inducing calcium phosphate nucleation; and Calcium phosphate. 2 . The composite material of claim 1 , wherein the elastin-like peptide comprises at least one olefinated residue prior to formation of the composite material.

3. The composite material according to claim 1 or 2, wherein the elastin-like peptide has the formula MW[VPGVGVPGMG(VPGVG)2] x , wherein x is an integer between 15 and 25, in particular between 19 and 21, more particularly equal to 20, and whose methionine residue is alkenylated before formation of said composite material.

4. The composite material according to any one of claims 1 to 3, wherein before the composite material is formed, the elastin-type peptide is of the formula MW[(VPGVG)(VPGMaG)(VPGVG)2] 20 The peptide ELPM80, wherein Ma represents an olefinated methionine residue of formula (III): 。 5. The composite material according to any one of claims 1 to 4, wherein the at least one bioactive peptide is an adhesion peptide capable of recruiting cells of interest.

6. The composite material according to any one of claims 1 to 5, wherein the at least one bioactive peptide is an adhesion peptide of the formula IKVAV-GGG-PVGLIG-GGG-YIGSR.

7. The composite material according to any one of claims 1 to 6, wherein the peptide capable of inducing calcium phosphate nucleation is a peptide having the sequence DSSEEKLFRRIGRFG.

8. The composite material according to any one of claims 1 to 6, wherein the peptide capable of inducing calcium phosphate nucleation is a peptide having the sequence DDDEEKFLRRIGRFG.

9. The composite material according to any one of claims 1 to 8, wherein the calcium phosphate corresponds to hydroxyapatite.

10. The composite material according to claim 9, comprising between 1 and 3% (w / v) hydroxyapatite. The composite material according to claim 9 , comprising 2% (w / v) hydroxyapatite.

12. The composite material according to any one of claims 1 to 11 for use in promoting innervation, osteogenesis and angiogenesis.

13. A composite material according to any one of claims 1 to 11 for use in controlling bone development.

14. The composite material according to any one of claims 1 to 11, which is used for repairing bone tissue.

Citation Information

Cited By

  • Collagen nerve repair material based on fusion protein controlled release as well as preparation method and application of collagen nerve repair material

    CN121422303A